2022
DOI: 10.3390/jof8030267
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Breakthrough Candidemia in an Immunocompromised Patient in Kuwait Due to Candida auris Exhibiting Reduced Susceptibility to Echinocandins and Carrying a Novel Mutation in Hotspot-1 of FKS1

Abstract: Candida auris is an emerging yeast pathogen that has recently caused major outbreaks in healthcare facilities worldwide. Clinical C. auris isolates are usually resistant to fluconazole and readily develop resistance to echinocandins and amphotericin B (AMB) during treatment. We describe here an interesting case of C. auris infection in an immunocompromised patient who had previously received AMB and caspofungin treatment. Subsequently, C. auris was isolated from tracheal (tracheostomy) secretions and twice fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 55 publications
4
27
0
Order By: Relevance
“…The FKS point mutations described in our study were detected previously (S639Y, S639P, and R1354H). Al-Obaid et al (2022) reported that isolates containing the S639Y or S639P mutation in hot-spot 1 of FKS1 exhibited reduced susceptibility to echinocandins, especially against micafungin [ 36 ]. Asadzadeh et al (2022) also described isolates with decreased sensitivity to echinocandins carrying an R1354H mutation in hot-spot 2 of FKS1 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FKS point mutations described in our study were detected previously (S639Y, S639P, and R1354H). Al-Obaid et al (2022) reported that isolates containing the S639Y or S639P mutation in hot-spot 1 of FKS1 exhibited reduced susceptibility to echinocandins, especially against micafungin [ 36 ]. Asadzadeh et al (2022) also described isolates with decreased sensitivity to echinocandins carrying an R1354H mutation in hot-spot 2 of FKS1 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FKS point mutations described in our study were detected previously (S639Y, S639P and R1354H). Al-Obaid et al (2022) reported that isolates containing the S639Y or S639P mutation in hot spot 1 of FKS1 exhibited reduced susceptibility to echinocandins, especially against micafungin. Asadzadeh et al (2022) also described isolates with decreased sensitivity to echinocandins carrying a R1354H mutation in hot spot 2 of FKS1.…”
Section: Discussionmentioning
confidence: 99%
“…Echinocandin resistance in C. auris mainly involves nonsynonymous mutations in the hotspot-1 (HS-1) and HS-2 regions of FKS1 encoding 1,3 β-D-glucan synthase. Most genetic alterations occur at codon 639 in HS-1 of FKS1 gene (Table 1 ) [ 43 , 60 , 71 , 78 , 79 ]. Two nonsynonymous mutations (F635L and F635Y) as well as deletion of codon F635 and D642Y mutation within HS-1 of FKS1 have been detected in some echinocandin-resistant C. auris [ 40 , 43 , 78 , 79 ].…”
Section: Identification Of C Auris In Yeast Cultur...mentioning
confidence: 99%
“…Most genetic alterations occur at codon 639 in HS-1 of FKS1 gene (Table 1 ) [ 43 , 60 , 71 , 78 , 79 ]. Two nonsynonymous mutations (F635L and F635Y) as well as deletion of codon F635 and D642Y mutation within HS-1 of FKS1 have been detected in some echinocandin-resistant C. auris [ 40 , 43 , 78 , 79 ]. Two nonsynonymous mutations (R1354S and R1354H) have also been found within HS-2 of FKS1 (Table 1 ) [ 43 , 79 ].…”
Section: Identification Of C Auris In Yeast Cultur...mentioning
confidence: 99%
See 1 more Smart Citation